Urgensi Perlindungan Hak Kekayaan Intelektual dalam Era Perdagangan Bebas - Gilang Ramadhan (Pusat Riset dan Inovasi Nasional, 2025)
Free trade provides significant opportunities for developing countries to increase exports, expand market access, and drive economic growth. Through engagement in global markets, products and services can reach a wider range of consumers, creating the potential for increased national income. However, global economic integration also presents serious challenges, particularly in terms of the protection of Intellectual Property Rights (IPR). As national boundaries in economic activity become increasingly blurred, intellectual property—including patents, trademarks, industrial designs, copyrights, and trade secrets—becomes increasingly vulnerable to infringement. Common forms of infringement include piracy, counterfeiting of branded products, and theft of technology or innovation. These practices not only harm creators or rights owners but can also hinder the development of innovation, reduce industrial competitiveness, and undermine consumer confidence. Adequate IPR protection requires a combination of strong national regulations and an effective international legal framework. Instruments such as the TRIPS (Trade-Related Aspects of Intellectual Property Rights) Agreement under the WTO provide global standards to which compliance must be adhered, but implementation at the national level is crucial for their success. Weak or inconsistent law enforcement can open the door to violations that harm both domestic and foreign businesses. Beyond legal aspects, effective IPR protection also impacts the investment climate. Investors tend to invest in countries that can guarantee the security of their intellectual assets. Therefore, IPR protection is not only a legal issue but also a long-term economic development strategy. Therefore, in the era of free trade, developing countries need to balance market openness with strengthening IPR protection systems to create a conducive environment for innovation, sustainable economic growth, and public welfare.